Empowering Education through Digital Leadership: The Evolving Role of School Principals - Chairul Anwar; Ahmad Aznem; Lidyawati Tandi Payung; Azainil; Dwi Nugroho Hidayanto (Al-Qalam Institue, 2025)
The digital transformation in education demands school principals to act as visionary, adaptive, and transformative digital leaders. Their role extends beyond providing infrastructure—it involves integrating technology into school management and the learning process. This study systematically examines the principal’s role as a digital leader in educational institutions and identifies existing research gaps. Using a literature review method, this study analyzes scholarly articles indexed in SINTA 1, Scopus, WoS, Elsevier, Springer, Taylor and Francis, Copernicus, and EBSCO from the past ten years. Inclusion criteria focused on digital leadership, educational leadership, and the role of principals. Thematic analysis revealed that digital leadership significantly enhances teaching quality, teachers’ digital literacy, and the development of a technology-driven school culture. Principals who embrace digital leadership foster innovation, collaboration, and more efficient resource management. However, challenges remain, including policy sustainability, teacher resistance to technology, digital access disparities, and limited research on digital ethics and security. The findings highlight the need for a supportive ecosystem involving government, educators, parents, and communities. This study recommends sustained digital leadership training, inclusive policymaking, and further exploration of the long-term impact of digital leadership on educational equity.